Deposition of Au nanoparticles inside porous CeO2 nanocubes using Langmuir-Blodgett technique - Das, Subhasis; Bhattacharjee, Gourab; Satpati, Biswarup; Kumar, Mukesh; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2018)
Porous 3D CeO2 nanocubes were synthesized using hot injection technique. These nanocubes were able to form a stable monolayer over water and HAuCl4 subphase in Langmuir-Blodgett (LB) trough due to the presence of surface capped oleic acid and oleylamine. CeO2-Au nanocomposites were synthesized exploiting the ability of oleylamine to reduce AuCl4 ions to Au-0, via LB method. CeO2 nanocubes gave rise to excellent long-range assembly at air/water interface and gold nanoparticles were formed inside these porous nanocubes without disturbing this arrangement. The formation of a stable monolayer was evidenced from the surface pressure-area (P-A) isotherm. The development of Au nanoparticles was confirmed with great effort from a comprehensive study using UV-Vis spectroscopy, XRD, XPS, FTIR, TEM, STEM, EDX, tomography and chemical mapping.

Direct thermal polymerization approach to N-rich holey carbon nitride nanosheets and their promising photocatalytic H-2 evolution and charge-storage activities - Antil, Bindu; Kumar, Lakshya; Reddy, K. P.; Gopinath, C. S.; Deka, Sasanka (ACS Sustainable Chemistry & Engineering, 2019)
Energy conversion and energy storage are two crucial challenges in green chemistry that have attracted tremendous attention for the last several decades. In this work, we have addressed both issues by synthesizing nitrogen-rich, few-layer-thick holey graphitic carbon nitride (g-C3N4) nanosheets by a simple, novel, direct thermal polymerization method, which is found to be very good in photocatalytic H-2 evolution reaction (energy-conversion) and charge-storage supercapacitor (energy-storage) applications. This as-synthesized conjugated polymer semiconductor (obtained stoichiometry C3N4.8) with unique structural and morphological advantages exhibits superior photocatalytic water splitting activity to H-2 evolution (2 620 mu mol h(-1) g(-1)) without the help of any cocatalysts under visible light in the presence of 20% triethanolamine (TEOA). The calculated apparent quantum yield is 8.5% at 427 nm, and the rate of photocatalytic hydrogen generation remained constant for nine consecutive catalytic cycles (9 h photocatalysis). The present material also shows electrochemical double layer capacitor (EDLC) behavior in alkaline electrolyte, where a symmetric coin cell device consisting of this electrode material without any large area support or conductive filler delivers high specific capacitance (275 F g(-1)), energy density (30 Wh kg(-1)), and power density (6651 W kg(-1)), and the supercapacitor cell can retain >98% capacitance efficiency up to 10 000 measured cycles at various current densities.
Keywords: g-C3N4; Hydrogen evolution; nanosheets; Photocatalyst; supercapacitor; water splitting

Directed holey and ordered g-C(3)N(4.5)nanosheets by a hard template nanocasting approach for sustainable visible-light hydrogen evolution with prominent quantum efficiency - Antil, Bindu; Ranjan, Ravi; Gopinath, Chinnakonda S.; Deka, Sasanka (Journal of Materials Chemistry A, 2020)
It is desirable yet challenging to synthesize a highly ordered holey carbon nitride material with excess nitrogen atoms for a sustainable solar H(2)evolution. Herein, we report the development of directed highly ordered nitrogen-rich honeycomb-like mesoporous carbon nitride nanosheets by using a novel synthetic approach for this purpose. The unique formation route, surface structure and charge carrier dynamics of the two dimensional holey nanosheets are comprehensively monitored and confirmed by SAXS, HRTEM, AFM, BET, XPS and TRPL analyses. Non-stoichiometric high nitrogen content mesoporous nanosheets with the final stoichiometry of g-C(3)N(4.5)acquiring a high specific surface area (382 m(2)g(-1)), remarkable pore size (7.2 nm) and sheet thickness similar to 5-6 nm are realized in this first report. This elegant material possesses unique low band-gap energy (2.42 eV). Remarkably, the as-synthesized g-C(3)N(4.5)NSs exhibit a record high photocatalytic H(2)evolution rate of 8180 mu mol g(-1)h(-1)under the present light irradiation (420 <=lambda <= 510 nm) condition. The apparent quantum efficiency is found to be as high as 27.14% at 420 nm and retains its photocatalytic activity for longer consecutive catalytic cycles. Bigger pore size and pore volume, and thin walls leading to shortening of the path length of exciton pairs, efficient charge separation and the prolonged average life time of the charge carriers, and lone electron pairs associated with the excess nitrogen content are found to be the reasons behind the excellent visible light driven water splitting reaction.